2014
DOI: 10.1188/14.cjon.396-399
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis of Falls in Patients Undergoing Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: To identify fall risks in patients undergoing hematopoietic stem cell transplantation (HSCT), the authors reviewed retrospective data on inpatients from April 2010 to March 2011. Among 77 HSCT patient records reviewed, the authors found that 35 patients had experienced at least one fall, including near-miss episodes (fallers). The main location of the falls was a corridor, and the main activity at the time of the fall was going to the toilet. To investigate fall risks along the HSCT time trajectory, the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Some previous studies reported that falls often occurred in the patients' rooms (1,3,(13)(14)(19)(20). In our study, 79.2% of falls occurred in patients' rooms, and !…”
Section: Discussionsupporting
confidence: 49%
“…Some previous studies reported that falls often occurred in the patients' rooms (1,3,(13)(14)(19)(20). In our study, 79.2% of falls occurred in patients' rooms, and !…”
Section: Discussionsupporting
confidence: 49%
“…In addition, six patients (46%) who were admitted for complications of BMT experienced continued strength loss after admission. Because weakness is a risk factor for falls, the degree of progressive weakness found in this study during the course of BMT might explain, in part, the finding by Ueki et al (2014) that patients undergoing allogeneic BMT had an increased risk of falling.…”
Section: Discussionmentioning
confidence: 68%
“…Patients undergoing BMT are at risk for falls. Ueki et al (2014) performed retrospective chart reviews on 77 patients who had received a BMT. The study found that 45% of the patients had sustained a fall while hospitalized, with about 70% of the falls occurring after engraftment, which was defined as more than three days of granulocyte counts of at least 5 x 10 8 /L.…”
Section: Background Weakness and Falls In Patients Undergoing Bone Mamentioning
confidence: 99%
“…32 By contrast, the incidence of fall in allo-HCT patients has not been studied extensively, with a single small study reporting a 45% incidence rate. 35 We have identified several predictors of transplant-related delirium and fall, including falls within the last year, advanced age, PIM use, impaired functional status, thrombocytopenia, and decreased creatinine clearance. Previous studies in general medical and surgical patients have identified prior cognitive impairment, severity of illness, high-risk medications, visual impairment, and malnutrition as significant risk factors for delirium, 32,36 as well as age, female sex, decreased mobility, visual impairment, cognitive impairment, and the use of psychotropic medication as significant risk factors for mechanical fall.…”
Section: Discussionmentioning
confidence: 99%